PERAN KOLABORASI SANGGAR HANGSUN GANDRUNG DALAM PENGEMBANGAN BUDAYA BANYUWANGI DI SURAKARTA - Lestari, Wundari (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to describe and analyze the role of collaboration initiated by Sanggar Hangsun Gandrung in promoting the development of Banyuwangi culture in Surakarta. The studio plays a significant role as a center for preserving Banyuwangi traditional dance and karawitan music outside its place of origin. Employing a qualitative method with an ethnographic approach, this research produces descriptive data. Data were collected through observation, interviews, and document analysis, using an interactive model for data analysis and source triangulation for data validation. The findings indicate that Sanggar Hangsun Gandrung engages in various forms of collaboration, including joint art performances, cultural workshops, educational initiatives, and cross-community and inter-institutional partnerships. These collaborative efforts are crucial in broadening the reach of Banyuwangi culture and enhancing public understanding of its traditional arts. Supporting factors for collaboration include a strong commitment to cultural preservation, open community networks, and the use of social media. Conversely, challenges faced include limited resources, insufficient institutional support, and differing visions among partners. Sanggar Hangsun Gandrung addresses these challenges through intensive communication, flexible cooperation, and strengthening community solidarity. This study concludes that collaboration serves as an effective strategy for sustaining local cultural identity in urban and cross-cultural settings such as Surakarta.